The relationship between farm size and fertilizer use efficiency: Evidence from China - Wei ZHU; Li-xia QI; Rui-mei WANG (Journal of Integrative Agriculture, 2022)
Low fertilizer use efficiency is commonly found in China's agriculture sector. It is critical to understand the drivers of fertilizer use in order to increase fertilizer use efficiency (FUE). The purpose of this paper is to investigate the relationship between farm size and FUE based on farm-level data in China. The results suggest a positive farm size–FUE relationship. The estimated elasticities of farm size for rice, maize, wheat–maize, and rice–maize are similar, and the average elasticity of farm size is around 0.2. Statistically, a 1% increase in farm size is associated with a 0.2% increase in FUE. The positive effect of farm size on FUE is not due to the increase in yield, but the reduction in fertilizer use while keeping yield largely unchanged. The findings suggest that promoting the expansion of farm size may increase FUE, and thus reduce environmental pollution caused by fertilizer overuse.